1983
DOI: 10.1111/j.1467-1770.1983.tb00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Acquisition of English as a Second Language Under Different Conditions of Exposure

Abstract: Claims have been made regarding the differing contributions of formal classroom versus naturalistic settings to second language acquisition (D'Anglejan 1978; Krashen 1976; Krashen and Seliger 1975; Sajavaara 1981). A study was designed to test such claims by investigating the production of English grammatical morphology by 18 adult native speakers of Spanish under three different conditions of exposure to English L2: (1) Instruction Only, (2) Naturalistic, and (3) Mixed (a combination of 1 and 2). Effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(146 citation statements)
references
References 23 publications
(23 reference statements)
11
128
1
4
Order By: Relevance
“…This study is significant because most studies involving the contributions of formal classroom instruction vs. informal naturalistic learning to SLA (Second Language Acquisition) have focused on investigating the grammatical accuracy of adult L2 learners (e.g., Krashen and Seliger 1975;Perkins and Larsen-Freeman 1975;Pica 1983;Turner 1979). As well as this, most studies that have examined L2 collocational knowledge have been carried out on classroom learners (either in EFL, or ESL, English Second Language, contexts).…”
Section: The Value Of This Researchmentioning
confidence: 99%
“…This study is significant because most studies involving the contributions of formal classroom instruction vs. informal naturalistic learning to SLA (Second Language Acquisition) have focused on investigating the grammatical accuracy of adult L2 learners (e.g., Krashen and Seliger 1975;Perkins and Larsen-Freeman 1975;Pica 1983;Turner 1979). As well as this, most studies that have examined L2 collocational knowledge have been carried out on classroom learners (either in EFL, or ESL, English Second Language, contexts).…”
Section: The Value Of This Researchmentioning
confidence: 99%
“…Unlike the early morpheme studies, these studies analysed the influence of the learning environment (Makino 1980;Pica 1983), the impact of age (Pak 1987), the use of learning strategies (Billings 1999) or, for example, the influence of affective factors (Wang 2000).…”
Section: Morpheme Order Studiesmentioning
confidence: 99%
“…According to this view of SLA, the controlling factor is the innate ability for learning language that all human beings possess. Pica (1983) determined that all language learners progressed through a fixed series of stages, known as developmental sequences, in learning particular linguistic subsystems, such as word order, negation, or relative clauses. In English negation, for example, when communicative samples were examined, it was revealed that both foreign language and second language learners progressed through the same fourstage sequence, defined in terms of placement of negation.…”
Section: Emphases In Second Language Research and Teachingmentioning
confidence: 99%